Answer:
K = x⁶ will be the substitution.
Explanation:
The given equation is
![4x^(12)-5x^(6)-14=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/c3pktcukmbpbdz5utu0oskjro82utvwzdu.png)
Now we have to convert it in a quadratic equation which should be in the form of
![ax^(2) +bx+c=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/4husygzl7qq21qxsephsnehd735wvug1y1.png)
We can rewrite the equation as
4(x⁶)² - 5(x⁶) - 14 = 0
Now we are clear that we have to substitute x⁶ = k to convert the equation in a quadratic equation
4K² - 5K - 14 = 0
Therefore, K = x⁶ will be the substitution.